Mitigasi Bencana Berbasis Sister Village Di Kawasan Rawan Bencana Gunung Merapi - Mujianto; Ria rajagukguk, jenni; Irwan Prasetyo (Magister Kajian Pembangunan Perkotaan dan Wilayah, 2023)
In an effort to reduce disaster risk, several villages on the upper slopes of Merapi have collaborated with villages below as evacuation sites, this term is then referred to as Sister Village or Paseduluran Village. Paseduluran Village is defined as a relationship like a sibling (sibling) between a village in a disaster area and a village that is free from a disaster, so that if one is forced to flee, the goal is to go to the sedulur (brother)'s place. The formation of the Paseduluran Village was outlined in the Decree of the Head of the BPBD of Klaten Regency Number 368 of 2019 concerning the Formation of the Paseduluran Village. In the SK it was stated that Balerante Village as the village of origin of the refugees collaborated with Kebondalem Lor Village as a buffer village. In Klaten District, there are 13 villages of origin for refugees, all of whom are from Kemalang District, and 26 villages receiving refugees, which are villages around the refugee shelters. The implementation of the Sister Village program is a form of community capacity and preparedness for disaster mitigation of the Mount Merapi eruption. Disaster mitigation itself is a series of efforts to reduce disaster risk, both through physical development and awareness and capacity building in dealing with disaster threats. So if the capacity and preparedness of the community is greater, it will reduce disaster risk.